Vaslui county in the national context: Evolution and effects of mobility of the working age population - Roxana Florina Munteanu (CES Working Papers, 2017)
The following paper shows the transition from internal to external migration and places Vaslui County into a spatial and time frame from the perspective of population mobility. Moreover, the consequences of the downgrading of internal migration by international migration are subject to the evolution of demographical and social indicators on which there are reflected: birth rate, general fertility, the rate of population growth, the index of demographical aging, because the involvement of the young population and young adult population in international migration led to a numerical decrease of the population with ages between 0-14, from 23,7% in 1990 to 15,0% in 2012, the increase of the majority of the old age population, of 65 years old and more, from 10,3% in 1990 to 15,0% in 2012 and of adult the population, 15-64 years old, from 66% in 1990 to 70% in 2012, according to National Institute of Statistics.
Keywords: E24; J21; J6; O15; 330; labour force; emigration; birth rate; Vaslui County